Pancasila dan Hukum Tata Negara untuk Menjaga Keseimbangan Antara Kebebasan dan Ketertiban Publik - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Dealova Rizki Meilana; Septiana Qholi Syainiah; Iftitah Naura Az Zahra; Afizal Fajariyadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This journal discusses the role of Pancasila in maintaining the balance between individual freedom and public order in Indonesian constitutional law. Pancasila, as the state foundation and ideology of the nation, occupies a central position in the formation of the legal system in Indonesia and serves as the source of all sources of law. In the context of constitutional law, Pancasila regulates how individual freedom is recognized as a constitutional right that is not absolute, but must be balanced with social responsibility and certain restrictions in order to maintain public interest and public order. This discussion highlights the challenges faced in maintaining this balance. This journal also provides suggestions for strengthening the normative foundation consistent with Pancasila, applying the principle of proportionality, strengthening the check and balance mechanism, and increasing public participation and legal education. Through the Historical Approach method, it is expected to examine the development of the rule of law and the principles of Pancasila from the past to the present.